Improving Students' Structure Mastery by Using Numbered Heads Together Cooperative Learning Strategy - Elyza Martiarini (Loquen, 2017)
The problems of this research were how to improve students’ structure mastery by using Numbered Heads Together cooperative learning strategy and how to motivate the students to apply it in English learning. The research type was a classroom action research. The subject consisted of 60 students of the third semester of English Department at University of Indraprasta PGRI in 2015-2016 academic year. The research data were collected by using pre-test and post-test. Data on students’ structure mastery were analysed by using descriptive and statistical analysis, to know the improvement in mean students. The result of cultivation data identified that the average score of post-test was 67.4 and the average score of pre-test was 55.5. It indicated that the score of post-test was higher than pre-test and teaching English language structure by using Numbered Heads Together can improve students’ structure mastery.